2002
DOI: 10.1080/713798348
|View full text |Cite
|
Sign up to set email alerts
|

Angioedema and systemic sclerosis

Abstract: We report a case of chronic idiopathic recurrent urticaria-angioedema and gastroesophageal reflux disease in a 35-years-old man, followed after 2 years by Raynaud's phenomenon and esophageal dysphagia, recurrent cough and dyspnoea, and after 4 years by systemic sclerosis. A review of the literature and possible correlated pathogenetic mechanisms are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, in most cases, aetiology of chronic urticaria is unknown; it is referred to as chronic idiopathic urticaria and in over one-third of cases the autoimmune pathogenic mechanism is proposed [2,3]. Interestingly, altered functions of the neuro-endocrine-immune system due to stress and other factors seem to appear as a very interesting theory for urticaria pathogenesis [4]. Changes in hormones balance and expression may promote the immunological imbalance and skin function responsible for urticaria expression.…”
Section: Introductionmentioning
confidence: 98%
“…However, in most cases, aetiology of chronic urticaria is unknown; it is referred to as chronic idiopathic urticaria and in over one-third of cases the autoimmune pathogenic mechanism is proposed [2,3]. Interestingly, altered functions of the neuro-endocrine-immune system due to stress and other factors seem to appear as a very interesting theory for urticaria pathogenesis [4]. Changes in hormones balance and expression may promote the immunological imbalance and skin function responsible for urticaria expression.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, it is known that, abnormalities in sex hormone metabolism and/or secretion may modulate activity of some immunologic and inflammatory diseases [30]. It has been suggested that dysfunction of the neuro-endocrine-immune environment may have a role in some cases of chronic urticaria [31]. Interestingly, we observed that serum DHEA-S concentration may be lower in chronic urticaria patients, regardless their gender and response to autologous serum skin test, as compared with sex-and age-matched healthy controls [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, hormones regulate the immune and inflammatory response, on the other hand, the inflammatory mediators influence the hormonal balance [5]. Interestingly, dysfunctions of the neuroendocrine–immune system due to stress and other factors seem to appear as a very interesting theory for urticaria pathogenesis [6]. It is known that urticaria may be associated with some diseases and/or influenced by some conditions characterized by sex hormonal changes, including menstrual cycle, pregnancy, menopause, and hormonal contraceptives or hormone replacement therapy.…”
Section: Introductionmentioning
confidence: 99%